Osseointegration of Ti-30Ta implants without primary stability: Effect of tranexamic acid - Rosifini Alves Rezende, Maria Cristina [UNESP]; Capalbo, Bruna Cabrera [UNESP]; Louzada, Mario Jefferson Quirino [UNESP]; Rangel, André Luiz Reis [UNESP]; Cintra, Luciano Ângelo [UNESP]; de Oliveira, João Augusto Guedes [UNESP]; Lisboa-Filho, Paulo Noronha [UNESP]; Wada, Cristiane Mayumi [UNESP]; Rosifini Alves Claro, Ana Paula [UNESP] (Trans Tech Publications, 2016)
A large clot formed between the inside of the bony wall of the extraction socket and the immediate implant surface may have premature breakdown. Tranexamic acid (TXA) is fibrinolysis inhibitor and an analog of the amino acid lysine. In this paper the influence of tranexamic acid on the osseointegration of Ti-30Ta implants without primary stability was investigated. Were fabricated 32 implants of CP Titanium Grade 4 and 32 implants of Ti-30Ta alloy with dimensions of 2.1 × 2.8mm Ø. Bone defects of 2.5×3.2 mm Ø were created in right tibia of 64 Wistar male-rats using a small round bur. They were divided (n=16) into: Group I (CP-Ti machined implant), Group II (CP-Ti machined implant/ tranexamic acid), Group III (Ti-30Ta implant) and Group IV (Ti-30Ta implant/ tranexamic acid). The surgical defects of the Group II and Group IV were bathed with 20 ml of the tranexamic acid solution. The animals were euthanized at 45 days postoperative. In the right tibia of half each group (8 animals/8 tibiae) the maximum torque value necessary for manual removal of each implant was measured in Newton centimeters (Ncm). The right tibia of other half each group was subjected to non-decalcified histology processing (Stevenel's blue/Alizarin red). Data were analyzed statistically (Kruskal-Wallis Analyses) and demonstrated significant differences (P<0.05) among groups. The values of group I were significantly lower than group III and IV, but without significant difference than group II both removal torque and peri-implant bone healing. The results suggest that: a) peri-implant bone formation occurred more rapidly around the Ti-30Ta implant; b) tranexamic acid favored the stabilization of blood clot and bone formation around Ti- 30Ta implants and not influenced bone formation around Ti-CP implants.
Keywords: Alloys; Tantalum; Titanium; Tranexamic acid; Wound healing